American Anthropology and Company : Historical Explorations - Murray, Stephen O. (Book collections on Project MUSE., 2013)
In American Anthropology and Company, linguist and sociologist Stephen O. Murray explores the connections between anthropology, linguistics, sociology, psychology, and history, in broad-ranging essays on the history of anthropology and allied disciplines. On subjects ranging from Native American linguistics to the pitfalls of American, Latin American, and East Asian fieldwork, among other topics, American Anthropology and Company presents the views of a historian of anthropology interested in the theoretical and institutional connections between disciplines that have always been in conversation with anthropology. Recurring characters include Edward Sapir, Alfred Kroeber, Robert Redfield, W. I. and Dorothy Thomas, and William Ogburn. While histories of anthropology rarely cross disciplinary boundaries, Murray moves in essay after essay toward an examination of the institutions, theories, and social networks of scholars as never before, maintaining a healthy skepticism toward anthropologists' views of their own methods and theories.